MSe / Si / C composite material, silicon negative electrode and preparation and application thereof

By using the preparation method of MSe/Si/C composite materials in silicon anode materials, the electron-ion conduction network is constructed, which solves the problem of volume expansion and poor cycle stability of silicon anode materials during circulation, and significantly improves its low-temperature fast charging performance and electrochemical performance.

CN119503736AActive Publication Date: 2025-02-25DALI CHENYU ENERGY STORAGE NEW MATERIALS CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411683261.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The silicon negative electrode material has problems such as volume expansion, poor cycle stability and low conductivity during the cycle, which limits its application in lithium-ion batteries.

Method used

Using the preparation method of MSe/Si/C composite material, by selenizing M-MOF and deposition of silicon on its substrate, an electron-ion conduction network is constructed to reduce the volume expansion of silicon.

Benefits of technology

It significantly improves the low-temperature fast charging performance of silicon negative electrode materials, improves electrochemical performance and cycle stability, and reduces volume expansion problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the field of silicon negative electrode battery materials, and particularly discloses a preparation method of an MSe / Si / C composite material, which comprises the following steps: mixing M-MOF and a selenium source for roasting reaction to obtain an MSe / C product; carrying out vapor deposition treatment on the MSe / C in a silicon source atmosphere to prepare an MSe / Si / C composite material; m is a transition metal element; the M-MOF is a metal frame material of transition metal elements. The invention also provides the material prepared by the preparation method and an application of the material in a battery. The process can induce uniform and effective deposition of silicon, facilitates in-situ construction of electron and ion conduction networks of M and Li2Se in the charge-discharge stage, and facilitates improvement of the low-temperature fast charge performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to battery negative electrodes, and in particular relates to the field of silicon negative electrode materials. Background Art

[0002] Lithium-ion batteries have a wide range of applications in modern electronic devices and play an important role in promoting the development of sustainable energy. First, lithium-ion batteries have a high energy density, which means that they can store more electrical energy in a smaller volume and weight, making them very suitable for portable electronic products. Secondly, they have a long cycle life and a low self-discharge rate, which makes them an ideal energy solution in electric vehicles and energy storage systems. In addition, with the global focus on reducing greenhouse gas emissions, lithium-ion batteries, as a key component of clean energy technology, can help increase the utilization of renewable energy sources such as solar and wind power. Therefore, research on lithium-ion batteries can not only promote technological progress, but also promote environmental protection and energy transformation.

[0003] The low energy density of lithium-ion batteries is mainly due to their working principles and material limitations. First, the energy density of lithium-ion batteries is limited by the lithium ion storage capacity of the positive and negative electrode materials. The theoretical specific capacity of the widely used graphite negative electrode material is 372mAh / g, and the theoretical specific capacity of positive electrode materials such as lithium cobalt oxide and lithium manganese oxide is also relatively limited. Secondly, the performance of the electrolyte and diaphragm materials also affects the energy density of the battery. They need to provide good ion conductivity while ensuring safety. In addition, battery design and manufacturing processes also have an impact on energy density, such as the space utilization inside the battery, the thickness and density of the electrode, etc. Finally, during the charging and discharging process of lithium-ion batteries, the volume expansion and contraction of the electrode materials will lead to the attenuation of battery life, which also indirectly limits the improvement of its energy density.

[0004] Compared with traditional graphite anodes, silicon anodes have a higher theoretical specific capacity, which is about ten times that of graphite. This means that in batteries of the same volume or weight, silicon anodes can store more electrical energy. In addition, the potential of the silicon anode is close to that of lithium, which helps to increase the voltage platform of the battery and thus increase the energy density of the battery. The silicon anode also has good conductivity and a low lithium ion diffusion barrier, which helps to improve the charge and discharge efficiency of the battery. However, the silicon anode has a large volume expansion problem during the cycle, which may lead to the destruction of the electrode structure and the shortening of the cycle life. Therefore, researchers are working hard to overcome these challenges through methods such as nanotechnology and composite material design to realize the application of silicon anodes in commercial lithium-ion batteries.

[0005] The current problems with silicon negative electrodes mainly include volume expansion, poor cycle stability and low conductivity. First, silicon undergoes significant volume changes during the insertion and extraction of lithium ions, which can lead to mechanical damage to the electrode material and shorten the battery life. Secondly, due to the volume expansion of silicon, the interface stability between the electrode and the electrolyte deteriorates during the cycle, which further affects the cycle life of the battery. Finally, the ionic conductivity and electronic conductivity of pure silicon are both low, which limits its electrochemical performance as an electrode material, especially affecting its low-temperature fast charging performance. Summary of the invention

[0006] In order to solve the problem that silicon materials are difficult to balance excellent electron-ion dual conduction capabilities and difficult to exert excellent low-temperature fast charging performance, the first purpose of the present invention is to provide a method for preparing a MSe / Si / C composite material, aiming to prepare an excellent electron-ion conduction network that can be constructed in situ, and significantly improve the low-temperature fast charging performance of silicon negative electrode materials.

[0007] The second purpose of the present invention is to provide a MSe / Si / C composite material prepared by the preparation method and its application in the preparation of lithium-ion batteries and silicon negative electrodes.

[0008] The third object of the present invention is to provide a silicon negative electrode comprising the MSe / Si / C composite material and its preparation method.

[0009] The fourth object of the present invention is to provide a lithium-ion battery comprising the MSe / Si / C composite material and an electrochemical formation method thereof.

[0010] The preparation method of the MSe / Si / C composite material comprises the steps of mixing M-MOF and a selenium source and performing a calcination reaction to obtain a MSe / C product; and then performing a vapor deposition treatment on the MSe / C in a silicon source atmosphere to obtain the MSe / Si / C composite material;

[0011] The M is a transition metal element; the M-MOF is a metal framework material of a transition metal element.

[0012] The present invention innovatively selenizes M-MOF to obtain a selenized product that retains the physicochemical structure of the M-MOF material, and further uses the selenized product as a substrate for silicon deposition, which is beneficial to the physicochemical structure of the selenized product and induces uniform and effective deposition of silicon. It is further used as a negative electrode material, which can in situ construct an electronic and ion conduction network of M and Li2Se during the charge and discharge stages, and can reduce the volume expansion problem of silicon, which can effectively improve the electrochemical properties of the material, especially its low-temperature fast charging performance.

[0013] In the present invention, the special framework structure of M-MOF is utilized for selenization, and an in-situ selenization product of the physicochemical structure can be constructed, which is beneficial to the subsequent deposition of silicon, and further to the in-situ construction of an ion-electron double network of the assembled battery during the first cycle of charge and discharge, and further to the improvement of the electrochemical properties of the obtained silicon-based material.

[0014] In the present invention, the M is at least one of Ni, Co, Fe, Zn and Mn.

[0015] Preferably, the M-MOF is at least one of ZIF-67, ZIF-8, and MOF-74.

[0016] Preferably, the M-MOF includes ZIF-67 and MOF-74; more preferably, the weight ratio of ZIF-67 to MOF-74 is 1:0.1 to 0.3. Studies have shown that the M-MOF of the present invention combined with the preparation process of the present invention can help further optimize the physical and chemical structure of the prepared product and help further enhance its low-temperature fast charging performance.

[0017] In the present invention, the selenium source is selenium powder.

[0018] Preferably, the weight ratio of the M-MOF to the selenium source is 1:0.1-1.5; more preferably 1:0.4-0.6.

[0019] In the present invention, the atmosphere in the calcining stage is a protective atmosphere.

[0020] Preferably, the calcination temperature is 600-1000°C, preferably 650-850°C; more preferably 650-750°C. Studies have shown that under the process described in the present invention, further combined with the joint control of the time, the physical and chemical structure of the material can be optimized, the material can be adapted to the low temperature requirements, and better low-temperature fast charging performance can be obtained.

[0021] Preferably, the holding time at the roasting temperature is 1 to 5 hours, preferably 2 to 4 hours.

[0022] In the present invention, the silicon source atmosphere contains at least one silicon-containing functional gas selected from silane, dichlorosilane and trichlorosilane. The silicon source includes silane and at least one auxiliary silicon source gas selected from dichlorosilane and trichlorosilane. Preferably, in the silicon source, the volume ratio of silane to auxiliary silicon source gas can be 1:0.1~0.2. Studies have shown that under the preferred process and conditions, it is helpful to induce and improve the deposition of silicon, and to further improve the performance of the prepared material under the requirements of low temperature and fast charging.

[0023] Preferably, the content of silicon-containing functional gas in the silicon source atmosphere is 20-80v%, and further can be 25-45v%.

[0024] Preferably, the temperature of the vapor deposition is 450-700°C, more preferably 500-600°C.

[0025] Preferably, the vapor deposition time is 1 to 5 hours, preferably 2 to 4 hours.

[0026] The invention also provides a MSe / Si / C composite material prepared by the preparation method.

[0027] The preparation method described in the present invention can give the prepared material special physical and chemical characteristics, and the material prepared by the preparation method can construct a special electron-ion conduction network in situ during the first charge and discharge stage, which can improve the expansion problem of silicon and effectively improve its electrochemical properties, especially its low-temperature fast charging performance.

[0028] The present invention also provides a silicon negative electrode, comprising a current collector and a negative electrode material composited on the surface thereof, wherein the negative electrode material comprises a negative electrode active material, and the negative electrode active material comprises the MSe / Si / C composite material of the present invention.

[0029] In the present invention, in addition to the MSe / Si / C composite material of the present application, the other components and contents of the silicon negative electrode can be well-known or reasonably controlled based on well-known principles and means.

[0030] For example, the content of the MSe / Si / C composite material in the negative electrode material is 70-95wt.%.

[0031] For example, the negative electrode material further includes a binder and a conductive agent.

[0032] The present invention also provides a pre-lithium-embedded and de-lithium-depleted silicon negative electrode, which is a silicon negative electrode obtained by inserting lithium and then de-lithiuming the silicon negative electrode described in the present invention; wherein the lithium insertion cutoff potential is 0.005~0.01V; and the lithium de-insertion cutoff potential is 1~1.2V.

[0033] Research in the present invention shows that the lithium insertion and delithiation treatment of the silicon negative electrode, combined with the joint control of the delithiation potential, is conducive to the in-situ construction of the ion-electron conduction network on silicon, which is beneficial to improving the electrochemical properties of the silicon material, especially effectively improving its low-temperature fast charging performance.

[0034] The present invention also provides a lithium-ion battery, comprising a battery cell composed of a positive electrode, a barrier layer and a negative electrode, wherein the negative electrode is the silicon negative electrode described in the present invention or the pre-lithium-embedded and de-lithium-de-silicon negative electrode.

[0035] In the lithium-ion battery of the present invention, when the negative electrode is a silicon negative electrode, the assembled lithium-ion battery is pre-electrochemically treated, wherein the electrochemical lithium insertion potential of the negative electrode side is 0.005-0.01V; and the lithium desorption potential is 1-1.2V.

[0036] The lithium-ion battery of the present invention, except for the silicon negative electrode of the present invention, may have other components and component structures that are well known.

[0037] Beneficial Effects

[0038] The present invention innovatively selenizes M-MOF and deposits silicon, which is beneficial to the physicochemical structure of the selenization product and induces uniform and effective deposition of silicon. It is further used as a negative electrode material, which can in situ construct the electronic and ion conduction network of M and Li2Se during the charge and discharge stage and reduce the volume expansion problem of silicon, which can effectively improve the electrochemical properties of the material, especially its low-temperature fast charging performance. DETAILED DESCRIPTION

[0039] The present invention will be described in detail below with reference to the embodiments, but the present invention is not limited thereto.

[0040] Example 1

[0041] Step 1:

[0042] ZIF-67 (M-MOF) and selenium powder in a weight ratio of 1:0.5 were reacted at 700°C under Ar for 3 h to obtain porous CoSe-C material.

[0043] Step 2:

[0044] The porous CoSe-C material was reacted in a 30V% silane (silicon source, specifically SiH4) and Ar mixed gas at 550°C for 3h to obtain a MSe / Si / C composite material with nano-silicon embedded in the porous substrate.

[0045] Step 3: Testing:

[0046] The composite material is used as the negative electrode material to make a pole piece, and the composite material obtained in the above Example 1 is used as the electrode material (negative electrode active material) to make an electrode slurry and a pole piece. The slurry ratio is electrode material: binder (CMC): conductive agent (SP) = 75:15:10. The slurry is evenly stirred and coated on a copper foil, and then dried under vacuum. The dried electrode sheet is used as the working electrode of the button battery, the lithium sheet is used as the counter electrode, and the electrolyte 1 M LiPF6 is dissolved in ethylene carbonate (EC): ethyl methyl carbonate (EMC): methyl propionate (MP) (20:60:20 v / v%) to assemble a battery. The battery is charged and discharged once, and the negative electrode side is controlled: 1.0V≤lithiation potential≤1.2V, and the lithium insertion potential is 0.005~0.01V, so that CoSe can be converted into Co+Li2Se in situ, thereby constructing a dual conductive substrate that conducts electrons and ions. The battery is then tested for electrochemical performance.

[0047] Example 2

[0048] Compared with Example 1, the only difference is that the M-MOF is changed. The experimental groups are:

[0049] Group A: M-MOF is MOF-74;

[0050] Group B: M-MOF is ZIF-67 and MOF-74 in a weight ratio of 1:0.2;

[0051] The amount of M-MOF used and other operations and parameters are the same as in Example 1.

[0052] Example 3

[0053] Compared with Example 1, the only difference is that the temperature of step 1 is 800° C., and the other operations and parameters are the same as those of Example 1.

[0054] Example 4

[0055] Compared with Example 1, the only difference is that the silicon source atmosphere in step 2 is changed. The experimental groups are:

[0056] Group A: The silicon source atmosphere is dichlorosilane;

[0057] Group B: The silicon source atmosphere is a mixture of silane and dichlorosilane in a volume ratio of 1:0.2;

[0058] Other operations and parameters are the same as in Example 1.

[0059] Example 5

[0060] Compared with Example 1, the only difference is that in step 1, the weight of M-MOF and selenium powder is 1:0.4; the insulation time is 2 hours; in step 2, the silane atmosphere content is 40v%, the deposition temperature is 600°C, and the deposition time is 2 hours; other operations and parameters are the same as in Example 1.

[0061] Example 6

[0062] Compared with Example 1, the only difference is that in the test of step 3, the delithiation potential of the first charge and discharge is 2.1V, and the other operations and parameters are the same as those in Example 1.

[0063] Comparative Example 1

[0064] Compared with Example 1, the only difference is that in step 1, no selenium powder is added, and other operations and parameters are the same as in Example 1.

[0065] Comparative Example 2

[0066] Compared with Example 1, the only difference is that M-MOF is carbonized in advance and then mixed with selenium powder for selenization. The temperature of carbonization and selenization are both 700°C, and the time is 1.5 hours respectively, to obtain a porous CoSe-C material. Other operations and parameters are the same as in Example 1.

[0067] Comparative Example 3

[0068] Compared with Example 1, the only difference is that a mixed raw material containing an M source (cobalt carbonate) and a carbon source (2-methylimidazole) in a molar ratio of 1:2 is used to replace the M-MOF in equal amounts, and other operations and parameters are the same as in Example 1.

[0069] The first lithium removal specific capacity and first coulombic efficiency of the above materials were tested at a current density of 0.2C, and the capacity was tested at a current of 0.2C. The ratio of the capacity at 2C and 0.2C was used as an indicator of its fast charge and discharge performance. The larger the value, the stronger the fast charge and discharge capability of the material. The constant current charge and discharge voltage range is 0.01-1.5V. The results are shown in Table 1:

[0070]

[0071] The present invention innovatively selenizes M-MOF, and further uses it as a substrate for silicon deposition, which can be beneficial to the physicochemical structure of the selenized product, induce uniform and effective deposition of silicon, and further use it as a negative electrode material, which can construct the electronic and ion conduction network of M and Li2Se in situ during the charge and discharge stage, and can reduce the volume expansion problem of silicon, so that the electrochemical properties of the material can be effectively improved, especially its low-temperature fast charging performance. In addition, it can be seen from Examples 1 and 2 of Table 1 that the use of the composite M-based MOF, in conjunction with the process of the present invention, is conducive to further optimizing the physicochemical structure adapted for low-temperature fast charging, and is conducive to further improving its low-temperature fast charging performance. In addition, it can be seen from Examples 1 and 4 that adding a certain halogen-containing silicon source atmosphere to the silicon source atmosphere can further optimize the low-temperature fast charging performance of the prepared material.

Claims

1. A method for preparing a MSe / Si / C composite material, characterized in that: The M-MOF and the selenium source are mixed and calcined to obtain a MSe / C product; the MSe / C is then subjected to a vapor deposition process in a silicon source atmosphere to obtain a MSe / Si / C composite material; The M is a transition metal element; the M-MOF is a metal framework material of a transition metal element.

2. The method for preparing the MSe / Si / C composite material according to claim 1, characterized in that: The M is at least one of Ni, Co, Fe, Zn and Mn; Preferably, the M-MOF is at least one of ZIF-67, ZIF-8, and MOF-74.

3. The method for preparing the MSe / Si / C composite material according to claim 1, characterized in that: The selenium source is selenium powder; Preferably, the weight ratio of the M-MOF to the selenium source is 1:0.1-1.

5.

4. The method for preparing the MSe / Si / C composite material according to claim 1, characterized in that: The atmosphere during the roasting stage is a protective atmosphere; Preferably, the calcination temperature is 600-1000°C; Preferably, the holding time at the roasting temperature is 1 to 5 hours.

5. The method for preparing the MSe / Si / C composite material according to claim 1, characterized in that: The silicon source atmosphere comprises at least one silicon-containing functional gas selected from silane, dichlorosilane and trichlorosilane; Preferably, the content of silicon-containing functional gas in the silicon source atmosphere is 20-80% by volume; Preferably, the temperature of the vapor deposition is 450-700°C; Preferably, the vapor deposition time is 1 to 5 hours.

6. A MSe / Si / C composite material obtained by the preparation method according to any one of claims 1 to 5.

7. A silicon negative electrode, comprising a current collector and a negative electrode material composited on the surface thereof, wherein the negative electrode material contains a negative electrode active material, characterized in that: The negative electrode active material comprises the MSe / Si / C composite material according to claim 6; Preferably, the content of the MSe / Si / C composite material in the negative electrode material is 70-95wt.%; Preferably, the negative electrode material further comprises a binder and a conductive agent.

8. A pre-lithium-embedded and lithium-de-lithium silicon negative electrode, characterized in that: The silicon negative electrode according to claim 7 is a silicon negative electrode which is subjected to lithium insertion and then lithium removal treatment; Among them, the cut-off potential of lithium insertion is 0.005~0.01V; the cut-off potential of lithium desorption is 1~1.2V.

9. A lithium-ion battery, comprising a battery cell composed of a positive electrode, a barrier layer and a negative electrode, characterized in that: The negative electrode is the silicon negative electrode according to claim 7 or the pre-lithium embedded and de-lithium silicon negative electrode according to claim 8.

10. The lithium ion battery according to claim 9, characterized in that When the negative electrode is a silicon negative electrode, the assembled lithium-ion battery is pre-treated with an electrochemical treatment, wherein the electrochemical lithium insertion potential of the negative electrode side is 0.005-0.01V; and the lithium desorption potential is 1-1.2V.

Citation Information

Patent Citations

  • Three-dimensional porous carbon-coated zinc selenide material for lithium ion battery anodes and preparation method of material

    CN106654221A

  • Cobalt silicon carbon sulfide compound, lithium ion battery cathode material and preparation method thereof

    CN110459744A

  • Preparation method of lithium-pre-embedded iron disulfide positive electrode material and lithium secondary battery

    CN112151770A

  • Silicon-based heterostructure material and preparation and application thereof

    CN114649533A

  • Silicon-carbon composite material, preparation method thereof, negative electrode material and lithium ion battery

    CN117352685A